2020
DOI: 10.1101/2020.03.14.20036061
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Epigenomics and Transcriptomics of Systemic Sclerosis CD4+ T cells reveal Long Range Dysregulation of Key Inflammatory Pathways mediated by disease-associated Susceptibility Loci

Abstract: System sclerosis (SSc) is a genetically complex autoimmune disease mediated by the interplay between genetic and epigenetic factors in a multitude of immune cells, with CD4+ T lymphocytes as one of the principle drivers of pathogenesis. In this study, we obtained DNA methylation and expression profiles of CD4+ T cells from 48 SSc patients and 16 healthy controls. Consequently, we identified 9112 and 3929 differentially methylated CpGs positions (DMPs) and differentially expressed genes (DEGs) respectively. The… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 91 publications
(105 reference statements)
1
10
0
Order By: Relevance
“…This is consistent with the recent finding that several tissue-specific repressed genomic regions enriched for disease-associated GWAS variants, and suggests that DMC may also have tissue-specific effect repressive regions [44]. Previous analyses of DNA methylation in other blood cell types and in larg European-descent groups [22,[51][52][53][54][55][56] report a larger difference in DNA methylation patterns between ca and controls, and an enrichment of genes involved in immune and inflammatory processes. In our study, o OAS3 and CD5 have been previously reported as differentially methylated in CD4+ T cells from Europ patients with SSc [56].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…This is consistent with the recent finding that several tissue-specific repressed genomic regions enriched for disease-associated GWAS variants, and suggests that DMC may also have tissue-specific effect repressive regions [44]. Previous analyses of DNA methylation in other blood cell types and in larg European-descent groups [22,[51][52][53][54][55][56] report a larger difference in DNA methylation patterns between ca and controls, and an enrichment of genes involved in immune and inflammatory processes. In our study, o OAS3 and CD5 have been previously reported as differentially methylated in CD4+ T cells from Europ patients with SSc [56].…”
Section: Discussionsupporting
confidence: 90%
“…Different metabolic perturbations are expressed in different patients, reflecting the clinical heterogeneity of SSc [90]. Our enrichment of genes involved in metabolic processes contrasts with the prominent enrichment of genes involved in immune and inflammatory processes consistently reported in both DNA methylation [22, 51-55, 82] and gene expression analyses in blood cell types and in largely European-descent groups, including in classical monocytes [38, 68-81]. The distinct racial category of the participants might appear as the most obvious explanation for this difference.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…This approach allows systematic identification of the promoter interactome (i.e., genomic regions, including distal regulatory regions, in physical proximity with more than 31,000 promoters) independently of the activity status of the interacting regions. This method has allowed us to uncover new aspects of the diversity of transcriptional regulatory factors 7 and mechanisms in cell differentiation 8,9 and disease 5 , and it has broadened our capacity to identify hundreds of potential new disease-candidate genes and/or gene pathways potentially deregulated by non-coding disease-associated variants 5,10,[11][12][13][14][15][16][17][18][19][20][21] . However, PCHi-C relies on the availability of millions of cells, typically ranging between 30-50 million cells per biological replicate, which prohibits the analysis of rare cell populations such as those commonly obtained in clinical settings.…”
Section: Introductionmentioning
confidence: 99%